Moralidade e plágio: um estudo com alunos do ensino médio - Romaneli, Mariana Santolin (2014)
Our purpose was to understand the judgment of plagiarism actions from students of the second and third years of high school, from public and private schools in Vitória, Espírito Santo. Subjects were 40 students between 16-18 years who attended three public and two private schools in Vitória-ES, equally divided as to sex and type of institution. Our survey instrument corresponded to a semistructured interview script, containing a fictitious story which involved the behavior of plagiarism. The interviews were conducted individually, in line with the Piagetian clinical method and we used the systematization of categories proposed by Delval as a procedure to analyze the protocols. We evaluated judgments of the adolescents regarding the action of plagiarism of the character of the story-told in the following respects: if he/she considered action as the right or wrong action, whether the plagiarist should or should not be punished and which penalty (ies) were suggested. The justifications of all aspects mentioned above were solicited. From the data we found that most students: 1) consider that plagiarism is a wrong attitude; 2) justify it being wrong especially for the "negligence of the student's in the fulfillment of his/her work", the "possibility of negative consequences" and for the "action being incorrect"; 3) state that the character "should be punished"; 4) analyzed as punishment for this act: "making a new work", "having a conversation" and "receiving a score of zero on the plagiarized work", and finally, 5) justified the sanctions suggested because of the "opportunity for the student to learn and / or reflect with the punishment", the “appropriateness of punishment" and "the possibility of negative consequences for the student". On the other hand, the reasons of the few students who felt that the character of the story "should not be punished" were in favor of a "lack of specification and / or prohibition by the teacher" and stated that it was because plagiarism is "common." In general, the data from our study show that participants know that plagiarism is wrong, recognize that one should not commit this act and most students penalized the conduct investigated. This work may contribute to the expansion of studies in the area of morality and contribute to the theoretical basis for the development of education projects in moral values that include in a general way academic dishonesty and specifically plagiarism. We believe that the inclusion of this content in the proposals for education in contemporary moral values can enrich the moral formation of students. So, we hope from the results found in this study,to support and promote further studies and provide discussions and actions on the said topic, especially in Psychology and Education.